PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPEMIMPINAN TRANSAKSIONAL DAN ETOS KERJA TERHADAP KOMITMEN ORGANISASI (STUDI KASUS PT AKINDO KARYA GEMILANG) - Marissa Yuliani (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
This study aims to determine the effect of transformational leadership, transactional leadership, and work ethic on organizational commitment. The population in this study are employees who work at PT Akindo Karya Gemilang Jakarta. The number of samples used was 92 respondents and data were collected using a questionnaire. The results of this study are that there is a positive and significant effect on Transformational Leadership on Organizational Commitment. This is evidenced by the t value of 2.813 where the value of 2.813> 1.98729 and the significant value of 0.006 where the value of 0.006 <0.05. There is no positive and significant influence of Transactional Leadership on Organizational Commitment. This is evidenced by the t value of 0.093 where the value of 0.093 <1.98729 and a significant value of 0.926 where the value of 0.926> 0.05. There is a positive and significant influence of the Job Ethic on Organizational Commitment. This is evidenced by the t value of 5.301 where the value of 5.301> 1.98729 and a significant value of 0.000 where the value of 0.000 <0.05. And there is a simultaneous and significant influence of Transformational Leadership, Transactional Leadership, Job Ethic on Organizational Commitment. This is evidenced by the calculated F value of 29.508 where the value of 29.508> F table 2.71 and a significant value of 0.000 where the value of 0.000 <0.05.